IKONITAS “BHINNEKA TUNGGAL IKA” DALAM MASYARAKAT EKONOMI ASEAN (MEA) - Hasyim, Muhammad; Hasbullah, Hasbullah; Isfajar, Isfahar (JURNAL ILMU BUDAYA, 2016)
This paper will discuss the study of iconity by pictures presenting the ASEAN Economic Community (AEC). Various iconities of the AEC pictures emerged, particularly in the virtual world (online) as a form of community support of ASEAN on the establishment of the ASEAN Economic community.Based on the semiotic study, the ASEAN Economic Community presented an iconity of bhinneka tunggal ika, which is togetherness and unity in the field of economic cooperation that comes from ASEAN countries against the background of different cultures and different languages. However, the discourse that emerges is of impending competition among the ASEAN members in the fields of trade and services. The hypothesis of the paper is that economic and cultural integration in ASEAN Economic Community has limited iconity. Key words: iconity, semiotic, culture, representation